Try hard! content analysis of senior middle school North Korean English textbooks through EIL perspectives - Ahn, Hyejeong; Yi, Marc Fei Yeo (Penerbit Universiti Kebangsaan Malaysia, 2024)
Textbooks provide rare insight into North Korea’s education system, where information access is scarce. Since its current leader, Kim Jong-Un, took power, North Korea has been placing increasing importance on English education, evidenced by major educational reforms that allocated more curriculum time to English, reduced the age of first contact with English education, and introduced more communicative approaches in English teaching. While it appears that North Korean education is becoming more internationalised, analysis of its English textbooks reveals otherwise. Using content analysis with the English as an International Language theoretical framework, this study investigates how English is refashioned as propaganda in North Korean education and whether North Korea’s English education prepares learners for global communication, by examining senior middle school English textbooks published during Kim Jong-Un's regime. Visuals in the textbook cover and text in the reading passages and textbook prefaces were analysed. The analysis revealed that these textbooks function concurrently as educational and propagandistic tools. They characterise English as an instrument for national development, enabling North Koreans to promote domestic culture abroad and access the wider scientific literature in English, achieving the state’s political goals of glorifying North Korean culture and boosting its international standing through technological advancements. These textbooks strategically advocate domestic topics and state-approved ideologies with little mention of global perspectives, reinforcing this information in a top-down fashion that, while equipping North Korean learners to communicate their own culture, precludes critical engagement with domestic and foreign cultures, limiting learners’ ability to use English in global, transcultural contexts.